Analysis of the use of user time based on access to bus boarding information at a BRT station - Sapacayo, Carlos (2023)
In many cities around the world, public transportation users must go to stops in advance due to the uncertainty of the bus boarding time. This causes them to stop investing their time in activities such as working, studying or leisure time. This research presents the analysis of the time it takes the average user to reach the station from their point of origin, the waiting times in electronic card recharge queues, the time it takes to reach the bus modules and the waiting time in boarding queues spent by users of a BRT station in Lima. Then, they are compared with an alternative to reduce waiting times based on access to precise information on the time of boarding. To do this, data from a survey carried out within the chosen station on the times of each phase were analyzed. Then, a comparison is made between the conventional situation and a scenario in which users know when they should go to the boarding modules to avoid wasting time. The results show that the proposed scenario reduces the time spent by users inside the BRT station from 22.57 minutes to 13.30 minutes compared to the current situation, which represents a reduction of 41.18%. Likewise, the waiting time in the proposed scenario for the boarding modules is 43% lower than the average time of users in the conventional situation. The current reduced times are significant, and, according to the survey results, these can be used in other activities such as leisure and work.